\(x^3+5x^2-4x-20=0\)
\(\Leftrightarrow x^2\left(x+5\right)-4\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x^2-4\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x-2\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=2\\x=-2\end{matrix}\right.\)
Vậy ...
Sửa đề lại nhé
\(x^3+5x^2-4x-20=0\)
\(\Leftrightarrow x^2\left(x+5\right)-4\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(x^2-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+5=0\\x^2-4=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-5\\x=\pm2\end{matrix}\right.\)
Vậy....................